The Impact of Policy Intensity on Overcapacity in Low-Carbon Energy Industry: Evidence From Photovoltaic Firms - Hu, Hui; Tang, Pei; Zhu, Yuqi; Hu, Dunwei; Wu, Yufeng (Frontiers in Energy Research, 2020)
This study evaluates the impact of policy intensity on overcapacity using listed Photovoltaic (PV) firms over the period 2011-2019 in China. We divide PV industrial chain into three segments, which are upstream, midstream and downstream. Results show that China's PV industry is diminishing returns to scale with low level of capacity utilization (20%). The enhancement of policy intensity can significantly promote overcapacity, but its impact varies in different policies and different enterprises. Fiscal subsidy has the largest positive effect in promoting overcapacity, followed by tax preference and land support. For three segments of PV industrial chain, fiscal subsidy, land support and tax preference play a significant role in promoting overcapacity in each segment; the increase in financial support exacerbates overcapacity in midstream. Furthermore, this study tests the effectiveness of an important PV policy posed by Chinese government in 2013. The results show that, the policy is inefficient in the short term. Nevertheless, it promotes the development of PV industry in the long term. It takes a long time to reduce positive effect of policies on overcapacity. This study provides a theoretical basis for the government to make comprehensive use of different policies.